2012
DOI: 10.1103/physrevlett.108.216803
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Hall Effect and Shubnikov–de Haas Oscillations in Highly DopedBi2Se3: Evidence for Layered Transport of Bulk Carriers

Abstract: Bi2Se3 is an important semiconductor thermoelectric material and a prototype topological insulator. Here we report observation of Shubnikov-de Hass oscillations accompanied by quantized Hall resistances (R(xy)) in highly doped n-type Bi2Se3 with bulk carrier concentrations of few 10(19) cm(-3). Measurements under tilted magnetic fields show that the magnetotransport is 2D-like, where only the c-axis component of the magnetic field controls the Landau level formation. The quantized step size in 1/R(xy) is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
163
5
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(211 citation statements)
references
References 36 publications
29
163
5
9
Order By: Relevance
“…This order of magnitude is consistent with Hall measurements on drop-casted Bi 2 Se 3 thin films and doping levels seen in previous studies of Bi 2 Se 3 thin films. [42,43] The contrast is most pronounced for frequencies below 1000 cm −1 , also in agreement with imaging measurements. Furthermore, this result conforms to the expected behavior of the far-field reflectivity calculated for carrier densities ranging from 10 18 to 10 20 cm −3 within our experimental measurement range ( Figure S4d, Supporting Information).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This order of magnitude is consistent with Hall measurements on drop-casted Bi 2 Se 3 thin films and doping levels seen in previous studies of Bi 2 Se 3 thin films. [42,43] The contrast is most pronounced for frequencies below 1000 cm −1 , also in agreement with imaging measurements. Furthermore, this result conforms to the expected behavior of the far-field reflectivity calculated for carrier densities ranging from 10 18 to 10 20 cm −3 within our experimental measurement range ( Figure S4d, Supporting Information).…”
Section: Resultssupporting
confidence: 71%
“…Here, we consider a two-layer system consisting of bulk SiO 2 , modeled in the spectral region of interest as a Lorentzian oscillator centered at ω = 1060 cm −1 ( Figure S4a , where n is the bulk 3D carrier density, e is the electron charge, and m is the effective mass. Using typical values for Bi 2 Se 3 , [41,42] we fix m = 0.14 m e and 1/τ = 600 cm −1 , and vary the carrier density to best fit the experimental trends seen in Figure 2d. Figure 2g shows the simulated near-field amplitude results of our two-layer s-SNOM model for a range of doping, where we choose demodulation at the second harmonic of the tip to match our SINS measurements, and normalize to Au.…”
Section: Resultsmentioning
confidence: 99%
“…103,104,108,170,171,184,[229][230][231] Since it is important to clarify this confusion, let us discuss this issue in some detail. In solids, the resistivity tensor is an inverse of the conductivity tensor, and in the isotropic case their relation is …”
Section: Quantum Oscillationsmentioning
confidence: 99%
“…In this regard, in the early stage of the TI research, the LL fan diagram analyses of the SdH oscillations observed in TIs were influenced by the case with graphene and used the minima in xx for indexing integer N. 103,104,108,170,171,184,[229][230][231] Therefore, the conclusions regarding the Berry phase in those early publications should be taken with care. It was Xiong et al who first switched to correctly using the minima in xx for the LL fan diagram analysis, 105) and some of the recent works performed reliable analyses and unambiguously demonstrated the Dirac nature of the surface state through determination of the Berry phase.…”
Section: Quantum Oscillationsmentioning
confidence: 99%
“…The gapless surface Dirac states will induce some quantum transport behavior in TIs that results in very large linear magnetoresistance (MR 6,7,17 and quantum oscillation with Landau sublevels 18 . In addition, in the highly doped TIs which have bulk carriers and exhibit metallic behavior, the competition between the contribution of the bulk carriers and the surface Dirac carriers could induce some interesting transport properties, such as the quantum Hall effect and layered transport of bulk carriers in doped Bi 2 Te 3 , 19 , and the field-induced polarized transport of valleys in ptyped Sb 2 Te 3 . 20 Especially in Bi 2 Se 3 crystals with bulk carriers, thermoelectric/thermomagnetic studies reveal the large Zeeman splitting of the three-dimensional bulk band and the variation of the chemical potential above the quantum limit.…”
Section: Introductionmentioning
confidence: 99%